Report of the twenty-fifth seáion of the European inland fisheries advisory commiáion. Antalya (Turkey). 21-28 May 2008 - FAO, Rome (Italy) (Rome (Italy), 2008)
Sumario (En)
Keywords: PESCA; RECURSOS PESQUEROS; PRODUCCION PESQUERA; DESARROLLO PESQUERO; ENTORNO SOCIOECONOMICO